Myocardial infarction after prostate cancer diagnosis in Norway: a population-wide registry-based study. (14th October 2021) - Forster, R; Kjellstadli, C; Myklebust, T.Å; Kvale, R
Abstract: Background: Survival after prostate cancer (PCa) is high for many patients, and it is now more likely they will die from cardiovascular disease than from PCa specific causes. However, patients with active malignancies have been excluded from trials to evaluate best treatments for myocardial infarction (MI). As people with PCa become a larger subpopulation of those experiencing a MI, clinicians need more comprehensive evidence regarding MI in people with PCa and if they are receiving optimal treatment. Purpose: To identify the Norwegian population diagnosed with PCa that have experienced a MI after their cancer diagnosis using routinely collected registry data, and describe relevant patient and treatment characteristics, as well as identify areas of missing data. Methods: We used data from Cancer Registry Norway to identify all people diagnosed with PCa between 2004 and 2019. Cancer data was linked with the Norwegian Myocardial Infarction Registry to identify PCa patients that were hospitalised for a MI as well as important features of the MI treatment period. Descriptive statistics were used to describe the number of people with PCa, important cancer specific features and variables related to the MI, as well as to explore missing data within collected variables. Results: We identified 70646 people diagnosed with PCa in Norway between 2004 and 2019, of which, 2929 (4.1%) experienced a MI (3465 MIs in total). Most had a single MI (2528, 86.3%), around 10.7% (314) had two MIs, and 3.0% (87) had three or more. Of all the MIs, 20.7% (718 in 700 patients) were classified as ST elevated MIs and 76.2% (2641 in 2218 patients) as non-ST elevated MIs (Table 1). Around 9% of patients were missing a baseline prostate specific antigen value and over 20% did not have an identified cancer stage. Thrombolysis and percutaneous intervention had a high number of records with unknown status of these treatments (58.5% and 36.6%, respectively). Conclusions: This population-wide registry-based study has demonstrated that linkage between Cancer Registry Norway and Norwegian Myocardial Infarction Registry provides a comprehensive dataset to further study the relationship between PCa and MI in the Norwegian population. This study benefits from data sourced from registries that have previously been found to be highly comprehensive and accurate. There was evidence of some variables with higher missing data, but we are confident that our planned further linkages with the Norwegian Cardiovascular Disease Registry and Norwegian Patient Registry, as well as using other clinical data, will help to overcome the current missing data issues. It is our plan to carry this research forward to provide a comprehensive, longitudinal analysis of how patients with PCa experience and are treated for an acute MI in Norway including PCa specific risk factors, comparison with current guidelines and if further guidelines should be created for people with PCa. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Norwegian Cancer SocietyNorwegian Institute of Public Health